Courses
Courses for Kids
Free study material
Offline Centres
More
Store Icon
Store

Prove the following identity, where the angles involved are acute angles for which the expressions are defined.
\[\dfrac{\cos A}{1+\sin A}+\dfrac{1+\sin A}{\cos A}=2\sec A\]

seo-qna
Last updated date: 20th Jun 2024
Total views: 396k
Views today: 10.96k
Answer
VerifiedVerified
396k+ views
Hint: To do this question, firstly we will LCM on the left hand side. Then, we will simplify the numerator of the fraction on the left hand side. After simplifying, we will use identity \[{{\sin }^{2}}\theta +{{\cos }^{2}}\theta =1\] for more simplification. After that, we will take the common factors out from both numerator and denominator and at last we will left with only \[2\sec A\]

Complete step by step answer:
In such questions, we prove them by either making the left hand side that is L.H.S. or by making the right hand side that is R.H.S. equal to the other in order to prove the proof that has been asked.
The below mentioned formulae may be used before solving, in the solution which is as follows
\[\begin{align}
  & \tan x=\dfrac{\sin x}{\cos x} \\
 & \cot x=\dfrac{\cos x}{\sin x} \\
 & \text{cosec}=\dfrac{1}{\sin x} \\
 & \sec x=\dfrac{1}{\cos x} \\
\end{align}\]
Now, these are the results that would be used to prove the proof mentioned in this question as using these identities, we would convert the left hand side that is L.H.S. or the right hand side that is R.H.S. to make either of them equal to the other.
In this particular question, we will first convert all the trigonometric functions in terms of sin and cos function and then we can convert the expression in terms of tan and cot function and then we will try to make the L.H.S. and the R.H.S. equal.
As mentioned in the question, we have to prove the given expression.
Now, we will start with the left hand side that is L.H.S. and try to make the necessary changes that are given in the hint, first, as follows
\[\Rightarrow LHS =\dfrac{\cos A}{1+\sin A}+\dfrac{1+\sin A}{\cos A}\]
\[\Rightarrow LHS =\dfrac{{{\cos }^{2}}A+{{\left( 1+\sin A \right)}^{2}}}{\left( 1+\sin A \right)\cdot \cos A}\]
\[\Rightarrow LHS =\dfrac{{{\cos }^{2}}A+1+{{\sin }^{2}}A+2\sin A}{\left( 1+\sin A \right)\cdot \cos A}\]
We know identity of trigonometry which is , \[({{\sin }^{2}}\theta +{{\cos }^{2}}\theta =1)\]
So, \[\Rightarrow LHS =\dfrac{1+1+2\sin A}{\left( 1+\sin A \right)\cdot \cos A}\]
\[\Rightarrow LHS =\dfrac{2\left( 1+\sin A \right)}{\left( 1+\sin A \right)\cdot \cos A}\]
\[\Rightarrow LHS =\dfrac{2}{\cos A}\]
\[\Rightarrow LHS =2\sec A\]
Now, as the right hand side that is R.H.S. is equal to the left hand side that is L.H.S., hence, the expression has been proved.

Note: Another method of attempting this question is by converting the right hand side that is R.H.S. to the left hand side that is L.H.S. by using the relations that are given in the hint. Through this method also, we could get to the correct answer and hence, we would be able to prove the required proof. Always remember some of the trigonometric identities such as \[{{\sin }^{2}}\theta +{{\cos }^{2}}\theta =1\], \[1+{{\tan }^{2}}\theta ={{\sec }^{2}}\theta \],\[1+{{\cot }^{2}}\theta ={\text{cosec}^{2}}\theta \]. Try not to make any calculation errors while doing the solution of the question.